Irradiance stress responses of gas exchange and antioxidant enzyme contents in pariparoba [Pothomorphe umbellata (L.) Miq.] plants - Marchese, J. A.; Mattana, R. S. [UNESP]; Ming, L. C. [UNESP]; Broetto, Fernando [UNESP]; Vendramini, P. F.; Moraes, R. M. (Springer, 2008)
We evaluated the growth and development of the medicinal species Pothomorphe umbellata ( L.) Miq. under different shade levels ( full sun and 30, 50, and 70 % shade, marked as I(100), I(70), I(50), and I(30), respectively) and their effects on gas exchange and activities of antioxidant enzymes. Photosynthetically active radiation varied from 1 254 mu mol m(-2) s(-1) at I(100) to 285 mu mol m(-2) s(-1) at I(30). Stomatal conductance, net photosynthetic rate, and relative chlorophyll (Chl) content were maximal in I(70) plants. Plants grown under I(100) produced leaves with lower Chl content and signs of chlorosis and necrosis. These symptoms indicated Chl degradation induced by the generation of reactive oxygen species. Stress related antioxidant enzyme activities ( Mn-SOD, Fe-SOD, and Cu/Zn-SOD) were highest in I(100) plants, whereas catalase activity was the lowest. Hence P. umbellata is a shade species ( sciophyte), a feature that should be considered in reforestation programs or in field plantings for production of medicinal constituents.
Keywords: catalase; chlorophyll; oxidative stress; photosynthesis; shade plants; stomatal conductance; superoxide dismutase; transpiration rate